Perbandingan Efektifitas Pemberian Kompres Madu dan Kompres Gula Kristal terhadap Penyembuhan Luka pada Tikus Putih - Winanda Rizki Bagus Santosa; Riyono Riyono (STRADA : Jurnal Ilmiah Kesehatan, 2018)
Honey and crystals sugar was complementary materials for wound care in a modern era. In other easy to get it, the curative characteristic in the honey and crystal sugar, it can to cure of the injury soon. The injury can easy to heal so the cost is cheap. This research aims to determine comparation of the effect of honey compress and crystals sugar compress on the process of wound healing in mice. This type of research is a True Experiment Randomized Design with research design Post Test Only Control Group Design conducted on 15 white rats received artificial injury. The sample selected by RCT (Randomized Control Trial) it divided into three groups, namely honey compress treatment group (n = 5), crystal sugar compress the treated group (n = 5), and the control group (n = 5). Independent variables that influence honey compress and the crystals sugar compress, while the dependent variable healed wound (edema, hyperemia, pus, granulation) on the observation every day for seven days. The data obtained, than it analyzed using Kolmogorov-Smirnov test by level of significance p <0.05. The results showed the influence statistic significantly granting of honey compress and sugar crystals compress third day of observation. Kolmogorov-Smirnov test (edema p = 0.013, hyperemia p = 0.013, pus p = 0.013, and granulation p = 0.013). Compresses can be summed giving honey and crystals sugar compress significantly effect the process of wound healing. Based on these results, it suggested in other that use a pack of honey or crystals sugar compress can be applied as comprehensive wound care